Prevalence and risk factors for agents causing diarrhea (Coronavirus, Rotavirus, Cryptosporidium spp., Eimeria spp., and nematodes helminthes) according to age in dairy calves from Brazil - Cruvinel, Leonardo Bueno; Ayres, Henderson; Zapa, Dina María Beltrán; Nicaretta, João Eduardo; Couto, Luiz Fellipe Monteiro; Heller, Luciana Maffini; Bastos, Thiago Souza Azeredo; Cruz, Breno Cayeiro [UNESP]; Soares, Vando Edésio; Teixeira, Weslen Fabricio; de Oliveira, Juliana Silva; Fritzen, Juliana Tomazi; et al. (Springer Nature, 2020)
The present study attempted to verify the prevalence of and risk factors for diarrhea-causing agents in dairy calves from Brazil. Additionally, ages with a higher risk of occurrence for each agent were verified by means of the receiver operating characteristic (ROC) curve. The collections were performed on 39 farms, belonging to 29 municipalities located in eight states of Brazil. It was possible to conclude that the prevalence of Coronavirus, Rotavirus, Cryptosporidium spp., Eimeria spp., and nematodes was 7.20% (95% CI 4.54–9.78), 6.37% (95% CI 3.85–8.89), 51.52% (95% CI 45.26–55.57), 3.46% (95% CI 2.24–4.67), and 3.46% (95% CI 2.24–4.67), respectively. Ages with higher probabilities of occurrence of these diseases in calves were < 10, > 8, > 6, > 37, and > 36 days, respectively. Diarrhea occurred more significantly (P < 0.0001) in animals less than 21 days old and mainly on those receiving milk through automatic feeders (P < 0.001). Cryptosporidium spp. were a risk factor for the occurrence of Rotavirus, and vice versa (P = 0.0039) and presented a positive correlation with Coronavirus (P = 0.0089). Calves that drink water from rivers, streams, and ponds had a higher chance of being infected by Eimeria spp. (P < 0.0001), as well as developing infection by nematodes (P < 0.0001). The results found in this study highlight the importance of studying the agents of diarrhea together, once they act as coinfection where the losses triggered for the owners will involve some of these agents simultaneously.
Keywords: Coronavirus; Cryptosporidium spp; Diarrhea; Eimeria spp; Nematodes; Rotavirus